Aspectos quimicos da polinização de especies do genero Clusia e sintese da (+)-cis-nortailoriona e 7S-isotiociano-7, 8-Di-hidro-alfa-bisaboleno - Oliveira, Cecilia Maria Alves de (1997)
Orientador: Anita Jocelyne Marsaioli